(untitled) (Discourse of Law and Administration, 2021)
The article entitled The controversy surrounding the concept of “minority” and the nature of its legal protection at the peace conference in Paris as well as during the interwar period in the light of the treaty provisions of the Paris conference of 1919 deals with the process of defining the meaning of the concept “minority” within the meaning of a group of the population of a country differing from the majority of a given country in terms of its race, religion or language at the Paris conference in 1919 and the attempts to interpret the concept from a legal-doctrinal and political perspective made by the League of Nations and the Permanent Court of International Justice in the interwar period. At the peace conference in Paris no definition of a national minority was developed in the meaning of a group of people differing from the majority of the society in the place of settlement in terms of a distinctly objective feature (religion, denomination, language), or a subjective sense of ethnicity or nationality, thus being aware of its own distinctness. Due to political reasons, representatives of the great powers decided to define the above population groups by using the terms: racial, religious or language minorities. The lack of a precise definition of the concept of national minorities or the criteria that define belonging to specific minority groups favored in the interwar period political instead of legal interpretations of its provisions relating to the type (kind) of a minority which may take advantage of the treaty protection, depending, in particular, on the party interpreting the concept (government authorities or representatives of minority groups concerned), its political views and affinity.